Curable resin composition, thin layer manufactured therefrom, color conversion panel including thin

By using specific silicon polymers and cured resin compositions with hollow particles, combined with low -temperature curing technology, the problem of thick film in the display device in the existing technology is solved. Thin layer manufacturing.

CN119350858APending Publication Date: 2025-01-24SAMSUNG SDI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410990399.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-24
Filing Date
2024-07-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to realize thick films with low refractive index, low haze and high mechanical properties in display devices, especially when the thickness increases, cracks are prone to occur.

Method used

A solid resin composition, which includes a silicon polymer, hollow particles and solvents represented by specific chemical formulas. It is a thin layer with low refractive index and low -fogging through low -temperature curing technology. The combination of Silicoline clusters improves the hardness and cracking resistance of the layers.

Benefits of technology

It is possible to manufacture thin layers with low refractive index, low haze and high mechanical properties in display devices, avoiding crack problems when the thickness increases, and improving luminous efficiency and anti-reflective properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350858A_ABST
    Figure CN119350858A_ABST
Patent Text Reader

Abstract

Disclosed are a curable resin composition, a thin layer manufactured from the curable resin composition, a color conversion panel including the thin layer, and a display device including the thin layer, the curable resin composition including a silicon-containing polymer represented by Chemical Formula 1 [Chemical Formula 1] (R4R5R6SiO1 / 2) M (R7R8SiO2 / 2) D (R9SiO3 / 2) T1 (SiO3 / 2-Y-SiO3 / 2) T2 (SiO4 / 2) Q, hollow particles, and a solvent.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2023-0096301 filed in the Korean Intellectual Property Office on July 24, 2023, the entire contents of which are incorporated herein by reference. Technical Field

[0003] Embodiments relate to a curable resin composition, a thin layer made therefrom, and a color conversion panel and a display device including the thin layer. Background Art

[0004] With the development of the display field, various display devices using displays have become more diverse, and among these display devices, there may be a continuous need for technologies to improve the luminous efficiency of self-luminous materials (e.g., organic light-emitting diodes (OLEDs)) or display devices including quantum dots. If a low-refractive material is used between the various thin layers of the panel forming the display, the luminous efficiency can be improved by recycling the light lost when the light moves inward. In addition, since the low-refractive property can cause a low-reflection effect, the low-refractive material can be used as a low-reflection layer of a lens outside a light sensor, or as an anti-reflection film (AR) film on the outermost layer of a display or solar cell.

[0005] Recently, display devices may need to be thinner, lighter, bendable and rollable, and the introduction of thin and flexible films to achieve these characteristics may be considered. The lower the refractive index of the low-refractive coating, the smaller the thickness of the coating, which can increase the margin of the coating and improve efficiency according to the purpose of the device. At the same time, if a display device is manufactured or used, in addition to the task of reducing the refractive index of the low-refractive material, it may also be necessary to improve thermal stability, require excellent adhesion to the upper film and the lower film, high transparency and crack resistance to prevent cracks at high thickness. Summary of the invention

[0006] The embodiment relates to a curable resin composition, the curable resin composition comprising: a silicon-containing polymer represented by Chemical Formula 1; hollow particles; and a solvent,

[0007] [Chemical formula 1]

[0008] (R 4 R 5 R 6 SiO 1 / 2 ) M (R 7 R 8 SiO 2 / 2) D (R 9 SiO 3 / 2 ) T1 (SiO 3 / 2 -Y-SiO 3 / 2 ) T2 (SiO 4 / 2 ) Q

[0009] Among them, in Chemical Formula 1, R 4 to R 9 are each independently hydrogen, or a substituted or unsubstituted C1-C30 alkyl group, a substituted or unsubstituted C2-C30 alkenyl group, a substituted or unsubstituted C2-C30 alkynyl group, a substituted or unsubstituted C1-C30 heteroalkyl group, a substituted or unsubstituted C6-C30 aryl group, a substituted or unsubstituted C3-C30 cycloalkyl group, a substituted or unsubstituted C2-C30 heterocycloalkyl group, a substituted or unsubstituted C1-C30 alkoxy group, a carboxyl group, R(C=O)-, R(C=O)O-, where R is hydrogen, a C1-C30 alkyl group, a C3-C30 cycloalkyl group, a C6-C30 aryl group or a combination thereof, a monovalent organic group containing an epoxy group, a (meth)acryloyloxy group, a (meth)acrylate group, an aminoalkyl group or a combination thereof, Y is a substituted or unsubstituted C1-C30 alkylene group, a substituted or unsubstituted C2-C30 alkenylene group, a substituted or unsubstituted C3-C30 cycloalkylene group, a substituted or unsubstituted C6-C30 arylene group or a combination thereof, 0≤M≤0.2, 0<D<0.2, 0.1<T1≤0.5, 0≤T2≤0.2, 0≤Q≤0.65, and M+D+T1+T2+Q = 1.

[0010] In Chemical Formula 1, 0≤M≤0.1, 0<D≤0.15, 0.2≤T1≤0.5 and 0.3≤Q≤0.65.

[0011] In Chemical Formula 1, 0≤M≤0.1, 0.01≤D≤0.1, 0.3≤T1≤0.45 and 0.5≤Q≤0.6.

[0012] The silicon-containing polymer may have a polystyrene-equivalent weight-average molecular weight of about 1,000 g / mol to about 100,000 g / mol.

[0013] Based on the total weight of the curable resin composition, the silicon-containing polymer may be included in an amount of about 1 wt% to about 50 wt%.

[0014] The curable resin composition may have a pH of about 4 to about 10.

[0015] The hollow particles may have an average diameter (D) of about 10 nm to about 300 nm. 50).

[0016] The hollow particles may have an average porosity of about 40% to about 90%.

[0017] The hollow particles may be hollow silica, and the silane compound may be included on the surface of the hollow silica.

[0018] The hollow particles may be included in an amount of about 1 wt % to about 35 wt % based on the total weight of the curable resin composition.

[0019] The curable resin composition may further include a fluorine surfactant or a silicone surfactant.

[0020] Embodiments may be realized by providing a thin layer made of the curable resin composition.

[0021] An embodiment may be implemented by providing a color conversion panel including the thin layer.

[0022] The embodiments may be implemented by providing a display device including the color conversion panel. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Various features will become apparent to those skilled in the art by describing in detail exemplary embodiments with reference to the accompanying drawings, in which:

[0024] Figure 1 is a plan view schematically illustrating a color conversion panel according to some embodiments.

[0025] Figure 2 is schematically shown along Figure 1 A sectional view of a cross section taken along line II-II in FIG.

[0026] Figure 3 is based on Figure 2 A cross-sectional view of a modified form of .

[0027] Figure 4 is based on Figure 2 and Figure 3 A cross-sectional view of a modified example of .

[0028] Figure 5 is based on Figure 2 A cross-sectional view of a modified form of .

[0029] Figure 6 is a transmission electron microscope (TEM) photograph showing that cracks do not occur in the cured layer according to Example 3 even when the thickness is about 4 μm or more.

[0030] Figure 7is a scanning electron microscope (SEM) photograph showing cracks occurring in a panel to which the cured layer according to Comparative Example 1 was applied.

[0031] Figure 8 is a SEM photograph showing cracks occurring in a panel to which a cured layer according to Comparative Example 2 was applied. DETAILED DESCRIPTION

[0032] Exemplary embodiments will now be described more fully below with reference to the accompanying drawings; however, exemplary embodiments may be implemented in different forms and should not be construed as limited to the embodiments described herein. Rather, these embodiments are provided to make this disclosure thorough and complete and to fully convey exemplary implementations to those skilled in the art.

[0033] In the drawings, the dimensions of layers and regions may be exaggerated for clarity of illustration. It is also understood that when a layer or element is referred to as being "on" another layer or substrate, the layer or element may be directly on the other layer or substrate, or there may be intervening layers. In addition, it is understood that when a layer is referred to as being "under" another layer, the layer may be directly under the other layer or there may be one or more intervening layers. In addition, it is also understood that when a layer is referred to as being "between" two layers, the layer may be the only layer between the two layers or there may be one or more intervening layers. In all drawings, the same reference numerals refer to the same elements.

[0034] Some embodiments relate to a curable resin composition that may also have excellent optical characteristics (eg, low refractive index and low haze) and excellent mechanical properties (eg, high indentation hardness and crack resistance).

[0035] As the display field develops, various display devices using displays have become more diversified, and among these display devices, there may be a continuous need for technology to improve the luminous efficiency of self-luminous materials (e.g., OLED) or display devices including quantum dots. Utilizing low refractive index properties, efficiency can be improved by reducing light losses inside the device through which light moves. In addition, the low refractive index material may have a low reflective property, so that the low refractive index material can be used as a low reflective layer of a lens outside a light sensor, or as an anti-reflective (AR) film on the outermost layer of a display or solar cell. At the same time, the lower the refractive index of the low refractive coating, the smaller the thickness of the coating can be, which can increase the margin of the coating and improve the efficiency of the device according to the purpose of the device.

[0036] Among other methods for obtaining low refractive index materials, if a thermosetting resin is used, the resin may be cured at a high temperature of about 350° C. or higher, or at least about 300° C. or higher, to form nanopores. Methods such as chemical vapor deposition (CVD) may not only require expensive equipment, but may also have difficulty in forming thick coatings, and may also have difficulty in producing nanopores, making it difficult to produce thin layers with low refractive indexes. If fluorine compounds or epoxy polymers are used, it may be difficult to achieve a low refractive index, and even if a low refractive index can be achieved, cracks are likely to occur if the thickness rises to the micrometer level.

[0037] In the case of silicon materials, it may be easy to implement a low refractive index, but as the thickness increases, the transparency of the coating may decrease and become turbid, and after exceeding a certain thickness (e.g., about 2.5 μm or more), cracks may begin to appear on the entire surface. In addition, even if the crack resistance of the low refractive index film can be improved, if the mechanical properties of the indentation hardness are not at least about 0.12 GPa or higher than 0.12 GPa, panel cracks may also occur. Specifically, if there is a layer with the same pattern as the color filter layer under the layer implementing the low refractive index, the substrate may be uneven and have steps due to the pattern. If the coating of the low refractive index layer fills the gaps between the steps of the lower pattern, the thickness of the low refractive index layer filled in the gap may become very thick. In this case, cracks may occur in the thickened low refractive index layer in the region. Therefore, it may be difficult to implement a thick film with a low refractive index and low haze characteristics, and no cracks and excellent mechanical properties.

[0038] The curable resin composition according to some embodiments may be cured at a low temperature (e.g., less than or equal to about 300° C., less than or equal to about 280° C., less than or equal to about 270° C., less than or equal to about 250° C., or less than or equal to about 240° C.), and the layer made from the curable resin composition may have a low refractive index (e.g., less than or equal to about 1.35) and a low haze (e.g., less than or equal to about 5%), thereby showing excellent optical properties, while exhibiting excellent indentation hardness (e.g., an indentation hardness of greater than or equal to about 0.12 GPa) and improved mechanical properties (e.g., high crack resistance (e.g., crack resistance at a thickness of greater than or equal to about 5 μm)). Therefore, the curable resin composition according to some embodiments may be advantageously used as a material for forming a low refractive index layer of various display devices (e.g., a display device including a quantum dot color filter having a step difference due to a pattern).

[0039] This curable resin composition may include a silicon-containing polymer satisfying a specific chemical formula, hollow particles, and a solvent as main components, and may further include an additive (eg, a surfactant) to improve coating properties and prevent unevenness.

[0040] Hereinafter, each component of the curable resin composition according to some embodiments will be described in detail.

[0041] (a) Silicon-containing polymers

[0042] Silicon-containing polymers may be referred to as low-refractive index materials, and the curable resin composition according to some embodiments may include a siloxane copolymer represented by Chemical Formula 1:

[0043] [Chemical formula 1]

[0044] (R 4 R 5 R 6 SiO 1 / 2 ) M (R 7 R 8 SiO 2 / 2 ) D (R 9 SiO 3 / 2 ) T1 (SiO 3 / 2 -Y-SiO 3 / 2 ) T2 (SiO 4 / 2 ) Q

[0045] In Chemical Formula 1, R 4 To R 9 Each independently may be or may include, for example, hydrogen, a substituted or unsubstituted C1 to C30 alkyl group, a substituted or unsubstituted C2 to C30 alkenyl group, a substituted or unsubstituted C2 to C30 alkynyl group, a substituted or unsubstituted C1 to C30 heteroalkyl group, a substituted or unsubstituted C6 to C30 aryl group, a substituted or unsubstituted C3 to C30 cycloalkyl group, a substituted or unsubstituted C2 to C30 heterocycloalkyl group, a substituted or unsubstituted C1 to C30 alkoxy group, a carboxyl group, R(C═O)—, R(C═O)O— (wherein R may be or may include, for example, hydrogen, a C1 to C30 alkyl group, a C3 to C30 cycloalkyl group, a C6 to C30 aryl group, or a combination thereof), an epoxy-containing monovalent organic group, a (meth)acryloyloxy group, a (meth)acrylate group, an aminoalkyl group, or a combination thereof.

[0046] Y may be or may include, for example, a substituted or unsubstituted C1-C30 alkylene group, a substituted or unsubstituted C2-C30 alkenylene group, a substituted or unsubstituted C3-C30 cycloalkylene group, a substituted or unsubstituted C6-C30 arylene group, or a combination thereof.

[0047] 0 ≤ M ≤ 0.2, 0 < D < 0.2, 0.1 ≤ T1 ≤ 0.5, 0 ≤ T2 ≤ 0.2, 0 ≤ Q ≤ 0.65.

[0048] M + D + T1 + T2 + Q = 1.

[0049] In Chemical Formula 1, 0 ≤ M ≤ 0.1, 0 < D ≤ 0.15, 0.2 ≤ T1 ≤ 0.5, 0 ≤ T2 ≤ 0.2, 0.3 ≤ Q ≤ 0.65 and M + D + T1 + T2 + Q = 1, for example, 0 ≤ M ≤ 0.1, 0.01 ≤ D ≤ 0.1, 0.3 ≤ T1 ≤ 0.45, 0 ≤ T2 ≤ 0.2, 0.5 ≤ Q ≤ 0.6 and M + D + T1 + T2 + Q = 1, or 0 ≤ M ≤ 0.1, 0.01 ≤ D ≤ 0.05, 0.35 ≤ T1 ≤ 0.45, 0 ≤ T2 ≤ 0.2, 0.55 ≤ Q ≤ 0.6 and M + D + T1 + T2 + Q = 1.

[0050] If the curable resin composition according to some embodiments includes a silicone copolymer as a polymer matrix, the layer made from the composition may have a low refractive index and low haze, thus maintaining high transparency while having a high indentation hardness and excellent crack resistance that inhibits the appearance of cracks even when the thickness increases.

[0051] In Chemical Formula 1, R 4 to R 9 may each independently be, for example, a substituted or unsubstituted C1-C10 alkyl group, a substituted or unsubstituted C3-C10 cycloalkyl group, a substituted or unsubstituted C2-C10 heterocycloalkyl group, a monovalent organic group containing an epoxy group, a substituted or unsubstituted C6-C20 aryl group, a (meth)acryloyl group, a (meth)acrylate group, an aminoalkyl group, a C1-C10 alkyl group substituted with a (meth)acryloyl group, a C1-C10 alkyl group substituted with a (meth)acrylate group, or a combination thereof.

[0052] In Chemical Formula 1, R 4 to R 9 may each independently be, for example, a C1-C4 alkyl group, a C2-C10 heterocycloalkyl group, a glycidyloxypropyl group, a C6-C10 aryl group, a (meth)acryloyl group, a (meth)acrylate group, a C1-C4 alkyl group substituted with a (meth)acryloyl group, a C1-C4 alkyl group substituted with a (meth)acrylate group, a C1-C4 alkyl group substituted with an amino group, or a combination thereof.

[0053] In Chemical Formula 1, Y may be, for example, a C1 to C10 alkylene group, a C4 to C10 cycloalkylene group, a C6 to C20 arylene group, or a combination thereof.

[0054] The polystyrene-equivalent weight average molecular weight of the siloxane copolymer represented by Chemical Formula 1 may be, for example, about 1,000 g / mol to about 100,000 g / mol, about 1,000 g / mol to about 90,000 g / mol, about 1,000 g / mol to about 80,000 g / mol, about 1,000 g / mol to about 70,000 g / mol, about 1,000 g / mol to about 60,000 g / mol, about 1,000 g / mol to about 50,000 g / mol, about 1,000 g / mol to about 60,000 g / mol, about 1,000 g / mol to about 70,000 g / mol, about 1,000 g / mol to about 80,000 g / mol, about 1,000 g / mol to about 90,000 g / mol, about 1,000 g / mol to about 110,000 g / mol, about 1,000 g / mol to about 120,000 g / mol, about 1,000 g / mol to about 130,000 g / mol, about 1,000 g / mol to about 150,000 g / mol, about 1,000 g / mol to about 160,000 g / mol, about 1 1 to about 40,000 g / mol, about 1,000 g / mol to about 30,000 g / mol, about 1,000 g / mol to about 20,000 g / mol, about 1,000 g / mol to about 10,000 g / mol, about 1,000 g / mol to about 9,000 g / mol, about 1,000 g / mol to about 8,000 g / mol, about 1,000 g / mol to about 7,000 g / mol, about 1,000 g / mol to about 6,000 g / mol, about 1,000 g / mol to about 0 g / mol to about 5,000 g / mol, about 1,500 g / mol to about 10,000 g / mol, about 1,500 g / mol to about 9,000 g / mol, about 1,500 g / mol to about 8,000 g / mol, about 1,500 g / mol to about 7,000 g / mol, about 2,000 g / mol to about 10,000 g / mol, about 2,000 g / mol to about 9,000 g / mol, about 2,000 g / mol to about 8,000 g / mol, about 2 ,000 g / mol to about 7,000 g / mol, about 2,000 g / mol to about 6,500 g / mol, about 2,000 g / mol to about 6,000 g / mol, about 2,000 g / mol to about 5,500 g / mol, about 2,000 g / mol to about 5,000 g / mol, about 2,000 g / mol to about 4,500 g / mol, about 2,500 g / mol to about 4,500 g / mol, or about 3,000 g / mol to about 4,500 g / mol.

[0055] Since the siloxane copolymer represented by Chemical Formula 1 may have a weight average molecular weight within the above range, a layer manufactured from the siloxane copolymer may have a low refractive index and may be less likely to generate cracks.

[0056] The siloxane copolymer represented by Chemical Formula 1 may be prepared by hydrolyzing and condensing a silane compound represented by the following Chemical Formula 2 and a carbosilane compound represented by Chemical Formula 3.

[0057] [Chemical formula 2]

[0058] (R 1 ) n -Si-(OR 2 ) 4-n

[0059] In chemical formula 2, R 1 The group may be or may include, for example, hydrogen, a substituted or unsubstituted C1 to C30 alkyl group, a substituted or unsubstituted C2 to C30 alkenyl group, a substituted or unsubstituted C2 to C30 alkynyl group, a substituted or unsubstituted C1 to C30 heteroalkyl group, a substituted or unsubstituted C6 to C30 aryl group, a substituted or unsubstituted C3 to C30 cycloalkyl group, a substituted or unsubstituted C2 to C30 heterocycloalkyl group, a substituted or unsubstituted C1 to C30 alkoxy group, a carboxyl group, R(C═O)—, R(C═O)O— (wherein R is hydrogen, a C1 to C30 alkyl group, a C3 to C30 cycloalkyl group, a C6 to C30 aryl group, or a combination thereof), an epoxy-containing monovalent organic group, a (meth)acryloyloxy group, a (meth)acrylate group, an aminoalkyl group, or a combination thereof.

[0060] R 2 It may be or may include, for example, hydrogen, or one of a C1 to C30 alkyl group, a C3 to C30 cycloalkyl group, a C2 to C30 alkenyl group, or a C6 to C30 aryl group.

[0061] 0≤n<4.

[0062] [Chemical formula 3]

[0063]

[0064] In chemical formula 3, R 3 Each independently may be or may include, for example, hydrogen, a C1 to C30 alkyl group, a C3 to C30 cycloalkyl group, a C2 to C30 alkenyl group, or a C6 to C30 aryl group.

[0065] Y may be or may include, for example, a substituted or unsubstituted C1 to C30 alkylene group, a substituted or unsubstituted C2 to C30 alkenylene group, a substituted or unsubstituted C3 to C30 cycloalkylene group, a substituted or unsubstituted C6 to C30 arylene group, or a combination thereof.

[0066] In Chemical Formula 2, n may be 0≤n≤3.

[0067] The hydrolysis polycondensation reaction of the silane compound represented by Chemical Formula 2 and the carbosilane compound represented by Chemical Formula 3 may be performed under an acid catalyst or a base catalyst in a solvent including water. In an embodiment, the hydrolysis polycondensation reaction may be performed under an acid catalyst.

[0068] In Chemical Formulae 1 to 3, “substituted” may mean that each functional group is substituted with an alkyl group, an alkenyl group, an alkynyl group, an aryl group, a hydroxyl group, a carboxyl group, an epoxy group, a (meth)acryloyl group, a (meth)acrylate group, a cyano group, a nitro group, a halogen group, or a combination thereof.

[0069] In chemical formula 2, R 1 The group may be, for example, a C1 to C10 alkyl group, a C3 to C20 cycloalkyl group, an epoxy-containing monovalent organic group, a C6 to C20 aryl group, a (meth)acryloyl group, a (meth)acrylate group, an alkyl group substituted with a (meth)acryloyl group, an alkyl group substituted with a (meth)acrylate group, an alkyl group substituted with an amino group, or a combination thereof.

[0070] In an embodiment, the silane compound represented by Chemical Formula 2 may include, for example, tetramethylorthosilicate (TMOS), tetraethylorthosilicate (TEOS), tetraisopropoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, diphenyldiethoxysilane, isobutyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, 3,3,3-trifluoropropyltrimethoxysilane, methyl-3,3,3-trifluoropropyldimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane Alkane, γ-glycidyloxytripropyl trimethoxysilane, γ-glycidyloxypropyl methyldiethoxysilane, γ-glycidyloxypropyl triethoxysilane, γ-methacryloxypropyl methyldimethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-methacryloxypropyl methyldiethoxysilane, γ-methacryloxypropyl triethoxysilane, N-β (aminoethyl) -γ-aminopropyl methyldimethoxysilane, N-β (aminoethyl) -γ-aminopropyl trimethoxysilane, N-β (aminoethyl) -γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, acryloxypropyl trimethoxysilane, trimethylsilanol (trimethylsilanol silanol), methyltrichlorosilane, methyldichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, phenyltrichlorosilane, diphenyldichlorosilane, trichloroethylenesilane, trimethylbromosilane, diethylsilane or the like.

[0071] In an embodiment, the carbosilane compound represented by Chemical Formula 3 may include, for example, 1,2-bis-trimethoxysilylethane, 1,2-bis-triethoxysilylethane, 1,4-bis-trimethoxysilylcyclohexane, or a similar material.

[0072] The siloxane copolymer represented by Chemical Formula 1 may be included in an amount of about 1 wt % to about 50 wt % (e.g., about 1 wt % to about 45 wt %, about 1 wt % to about 40 wt %, about 1 wt % to about 35 wt %, about 5 wt % to about 50 wt %, about 5 wt % to about 45 wt %, about 5 wt % to about 40 wt %, about 5 wt % to about 35 wt %, about 10 wt % to about 50 wt %, about 10 wt % to about 45 wt %, about 10 wt % to about 40 wt %, about 10 wt % to about 35 wt %, about 15 wt % to about 50 wt %, about 15 wt % to about 45 wt %, about 15 wt % to about 40 wt %, about 15 wt % to about 35 wt %, about 20 wt % to about 50 wt %, about 20 wt % to about 45 wt %, about 20 wt % to about 40 wt %, about 20 wt % to about 35 wt %) based on the total weight of the curable resin composition.

[0073] Since the siloxane copolymer represented by Chemical Formula 1 may be included in the curable resin composition according to some embodiments in the above range, a layer manufactured from the curable resin composition may exhibit low refractive index and low haze and may have mechanical properties (eg, high pressure scratch hardness and excellent crack resistance).

[0074] (b) Hollow particles

[0075] The curable resin composition according to some embodiments may include hollow particles to further reduce the refractive index of the layer. The hollow particles may be hollow particles of a metal oxide (eg, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, or zinc oxide), and may be hollow silica particles.

[0076] The siloxane copolymer included in the curable resin composition according to some embodiments may itself have low refractive index characteristics, and if hollow particles are mixed with such siloxane copolymer, the refractive index of a layer manufactured from the resin composition may be further reduced due to pores within the hollow particles.

[0077] In an embodiment, a silane compound, for example, may be included on the surface of the hollow silica particles. If the surface of the hollow silica particles is treated with a silane compound (e.g., a silane compound represented by Chemical Formula 2 for preparing a siloxane copolymer included in a curable resin composition), the silane compound may be bonded to the surface of the hollow silica particles. The hollow silica particles comprising a silane compound on the surface may further improve the compatibility with the siloxane copolymer in the curable resin composition. In an embodiment, the silane compound capable of bonding to the surface of the hollow silica particles may be, for example, methyltrimethoxysilane or methacryloxypropyltrimethoxysilane.

[0078] The method of bonding the silane compound to the surface of the hollow silica particles can be any suitable method. In an embodiment, the silane compound can be dissolved or dispersed in a suitable solvent (e.g., water, ethanol or other suitable polar organic solvent) at an appropriate concentration, and then the hollow silica particles can be added to this solution and stirred to react. In addition to these methods, particles in which the silane compound can be bonded to the surface of the hollow silica particles can also be manufactured by various suitable methods.

[0079] The average diameter of the hollow silica particles (D 50 ) may be from about 10 nm to about 300 nm, for example, from about 10 nm to about 250 nm. Maintaining the average diameter size of the hollow silica particles within the above range can help ensure that the hollow silica particles can be well dispersed in the curable resin composition including the siloxane copolymer according to some embodiments, can effectively reduce the refractive index of the cured layer, and can achieve the effect of increasing the indentation hardness of the layer or improving the crack resistance of the layer.

[0080] The porosity of the hollow silica particles may be, for example, about 40% to about 90% or about 40% to about 80%.

[0081] The hollow silica particles may be included in an amount of about 1 wt % to about 35 wt % (e.g., about 1 wt % to about 30 wt %, about 5 wt % to about 35 wt %, about 5 wt % to about 30 wt %, about 10 wt % to about 35 wt %, about 10 wt % to about 30 wt %, about 15 wt % to about 35 wt %, about 15 wt % to about 30 wt %, about 20 wt % to about 35 wt %, or about 20 wt % to about 30 wt %) based on the total weight of the curable resin composition according to some embodiments.

[0082] (c) Solvent

[0083] The solvent included in the curable resin composition according to some embodiments can be used alone or in a mixture of two or more solvents. The solvent can be an organic solvent, such as an alcohol (e.g., 4-methyl-2-pentanol, 4-methyl-2-propanol, 1-butanol, methanol, isopropanol or 1-propanol), an ether (e.g., anisole, tetrahydrofuran, diethylene glycol methyl ethyl ether or triethylene glycol monomethyl ether), an ester (e.g., n-butyl acetate, propylene glycol monomethyl ether acetate, ethyl acetate or ethyl lactate), a ketone (e.g., γ-butyrolactone, methyl ethyl ketone or 2-heptanone) or a mixture thereof.

[0084] The solvent may be included in an amount of about 30 wt % to about 95 wt % (e.g., about 30 wt % to about 90 wt %, about 35 wt % to about 90 wt %, or about 40 wt % to about 90 wt %) based on the total weight of the curable resin composition, and may be appropriately adjusted depending on the total solid content.

[0085] (d) Other additives

[0086] The curable resin composition according to some embodiments may further include various additives known in the art. These additives may also include, for example, surfactants (e.g., fluorosurfactants or silicone surfactants) to improve coating properties and prevent defects when the composition is coated. These additives may be included in an amount of about 0.1 wt % to about 3 wt % based on the total curable resin composition.

[0087] Some embodiments may provide a thin layer manufactured by curing the curable resin composition.

[0088] Some embodiments may provide a color conversion panel including the thin layer.

[0089] The color conversion panel may include, for example: a substrate; a low refractive index layer located on one surface of the substrate; a color conversion layer including a color conversion member disposed on the low refractive index layer or between the low refractive index layer and the substrate; and a planarization layer covering the low refractive index layer and the color conversion layer, wherein the low refractive index layer may be manufactured from a curable resin composition according to some embodiments.

[0090] Herein, since the curable resin composition may be the same as described above, a detailed description thereof will not be repeated.

[0091] In an embodiment, the low refractive index layer of the color conversion panel can be manufactured by coating a substrate or a color conversion layer with a curable resin composition according to some embodiments and curing it. In an embodiment, if the curable resin composition is coated on a substrate or a color conversion layer formed on a substrate, the curable resin composition can be dried and cured at a temperature of greater than or equal to about 150° C. and less than or equal to about 250° C. (e.g., greater than or equal to about 170° C. and less than or equal to about 250° C., greater than or equal to about 180° C. and less than or equal to about 250° C., greater than or equal to about 180° C. and less than or equal to about 240° C., greater than or equal to about 190° C. and less than or equal to about 240° C., greater than or equal to about 200° C. and less than or equal to about 240° C., greater than or equal to about 210° C. and less than or equal to about 240° C., or greater than or equal to about 220° C. and less than or equal to about 240° C.) for about 10 minutes to about 1 hour.

[0092] The method of coating the composition on the substrate or the color conversion layer may be any suitable method, such as spin coating, slot coating and spin coating, slot coating, roller coating or die coating. In an embodiment, the composition may be spin coated on the substrate or the color conversion layer.

[0093] The low refractive index layer manufactured as above may have a thickness of about 100 nm to about 10 μm. In an embodiment, the thin layer may have a thickness of about 1 μm to about 10 μm (eg, about 1 μm to about 8 μm, about 1 μm to about 7 μm, or about 1 μm to about 6.5 μm).

[0094] Hereinafter, a color conversion panel according to some embodiments will be explained in detail with reference to the accompanying drawings.

[0095] Figure 1 is a plan view schematically showing a color conversion panel 100 according to some embodiments, and Figure 2 and Figure 3 Along the Figure 1 A schematic cross-sectional view taken along line II-II is shown.

[0096] Reference Figure 2 and Figure 3 According to some embodiments, the color conversion panel 100 may include a substrate 110, a low refractive index layer 120, a color conversion layer 130, and a planarization layer 140, wherein the color conversion layer 130 may include a color conversion layer that emits at least two different wavelengths of light, for example, a first color conversion layer 132 that emits a first wavelength of light in a first region A and a second color conversion layer 134 that emits a second wavelength of light in a second region B. In an embodiment, the first color conversion layer 132 may emit red (R) light, and the second color conversion layer 134 may emit green (G) light. In an embodiment, the color conversion panel 100 may further include a third region C that emits blue (B) light or white light.

[0097] Substrate 110 may be made of a transparent and electrically insulating material, and may further include a protective layer 112 at positions corresponding to first color conversion layer 132 and second color conversion layer 134. Protective layer 112 may be formed on one surface of substrate 110, and if color conversion layer 130 is formed on substrate 110, protective layer 112 may help ensure that the color conversion layer can be patterned smoothly, and may help protect color conversion components inside the color conversion layer.

[0098] The low refractive index layer 120 may cover a portion of the substrate 110 and the protective layer 112 on one surface of the substrate 110 (eg, one surface of the substrate 110 on which the protective layer 112 may be formed), or Figure 3As shown in , the color conversion layer 130 may be first stacked on the protective layer 112, and then the low refractive index layer 120 may be stacked on the color conversion layer 130 to cover the entire color conversion layer 130, a portion of the substrate 110, and a portion of the protective layer 112. That is, in Figure 2 and Figure 3 The only difference is that the low refractive index layer 120 can be located below the color conversion layer 130 (in Figure 2 Alternatively, the low refractive index layer 120 may be located on the color conversion layer 130. This may be Figure 2 and Figure 3 The only difference between the two, and all other components can be the same.

[0099] The low refractive index layer 120 according to some embodiments may have a relatively low refractive index of about 1.35 or less (e.g., about 1.32 or less, about 1.31 or less, about 1.30 or less, about 1.29 or less, about 1.28 or less, about 1.27 or less, about 1.26 or less, about 1.25 or less, about 1.24 or less, or about 1.23 or less) for a wavelength of about 500 nm to about 550 nm. Forming the low refractive index layer 120 on the upper or lower surface of the color conversion layer 130 or on both the upper and lower surfaces of the color conversion layer 130 may help ensure that light emitted from the color conversion layer 130 may be prevented from being reflected toward the substrate 110. In an embodiment, when light passes through the low refractive index layer 120, the light may be reflected or refracted due to the difference in refractive index and may move back toward the color conversion layer 130, thereby causing an effect of reusing the lost light. In an embodiment, the luminous efficiency of the color conversion panel 100 according to some embodiments in which the low refractive index layer 120 may be formed on the upper surface or the lower surface of the color conversion layer 130 or on both the upper surface and the lower surface of the color conversion layer 130 may be further improved. The refractive index mentioned in this specification refers to an absolute refractive index representing the ratio of the speed of light in a vacuum to the speed of light in a medium.

[0100] In addition, the low refractive index layer may have an average light transmittance of greater than or equal to about 90% (e.g., greater than or equal to about 91%, greater than or equal to about 92%, greater than or equal to about 93%, greater than or equal to about 94%, greater than or equal to about 95%, greater than or equal to about 96%, greater than or equal to about 97%, greater than or equal to about 98%, or greater than or equal to about 99%) for wavelengths from about 400 nm to about 800 nm. Maintaining the average light transmittance of the low refractive index layer for wavelengths from about 400 nm to about 800 nm within the above range can help ensure that the optical properties of the low refractive index layer can be further improved.

[0101] In an embodiment, the low refractive index layer may have an average reflectivity (excluding specular component exclude (SCE) value) of about 10% or less (e.g., about 7% or less, about 5% or less, or about 3% or less) over the entire wavelength range of about 400 nm to about 800 nm corresponding to the visible light range. In an embodiment, the color conversion panel 100 according to some embodiments may have high light transmittance even in a low wavelength range, and may maintain low reflectivity over the entire region of visible light wavelengths to further improve optical characteristics.

[0102] The first color conversion layer 132 and the second color conversion layer 134 may include a first color conversion member 133 emitting light of a first wavelength and a second color conversion member 135 emitting light of a second wavelength, respectively, and each of the first color conversion member 133 and the second color conversion member 135 may include quantum dots that convert the wavelength of incident light into light of other wavelengths. These color conversion members may be formed by applying a composition for forming a color conversion layer including quantum dots to a substrate or the low refractive index layer 120 formed on the substrate. The composition for forming the color conversion layer may include quantum dots, a binder resin, a photopolymerizable monomer, a photopolymerization initiator, a solvent, or other additives.

[0103] In an embodiment, the color conversion layer 130 may be formed by applying a composition for forming a color conversion layer including the color conversion member 133 and the color conversion member 135 including quantum dots to the substrate 110 or the low refractive index layer 120 formed on the substrate 110, and then performing a patterning process. The patterning process may be performed in such a manner as to obtain a pattern excellent in heat resistance, light resistance, adhesion, crack resistance, chemical resistance, high strength, storage, or stability: the composition for forming a color conversion layer is applied to the substrate 110 or the low refractive index layer 120 by a method such as spin coating or slit coating, roll coating, screen printing, or an applicator method and dried to form a coating layer; exposure is performed to form a pattern of a shape corresponding to the first color conversion layer 132 and the second color conversion layer 134 using a mask; development is performed to remove unnecessary portions; and a post-treatment step of curing by heating again or irradiating active rays is performed.

[0104] In addition to the color conversion member 133 and the color conversion member 135 including quantum dots, the first color conversion layer 132 and the second color conversion layer 134 may further include a light scatterer. The light scatterer may be dispersed in the color conversion layer 130 together with the quantum dots. The light scatterer may induce incident light to reach the quantum dots or the radiation direction, so that the radiation light emitted from the quantum dots may be emitted from the color conversion layer 130 to the outside. Thus, the reduction in the luminous efficiency of the color conversion layer 130 may be minimized. The transmission member 136 may further include a light scatterer.

[0105] The planarization layer 140 may be formed on the low refractive index layer 120 and the color conversion layer 130. The planarization layer 140 may cover the low refractive index layer 120 and the color conversion layer 130 to protect them and planarize the surface of the color conversion panel 100. The planarization layer 140 may be made of a transparent and electrically insulating material so that light can be transmitted. In an embodiment, the planarization layer 140 may be made of a polymer matrix that is the same as or different from the low refractive index layer 120. In an embodiment, the planarization layer 140 may be made of a low refractive index material including a carbosilane-siloxane copolymer like the low refractive index layer 120, and thus the light emitting efficiency of the color conversion panel 100 may be further improved. In an embodiment, if the incident light of the low refractive index layer 120 enters the planarization layer 140, reflection or scattering may be minimized, and thus the optical loss at the interface may be minimized to provide a color conversion panel 100 with improved light efficiency.

[0106] In an embodiment, the color conversion layer 130 may further include a transmissive member 136 corresponding to the third region C. The transmissive member 136 itself may emit light received from the light source without performing a separate color conversion. In an embodiment, the transmissive member 136 may be formed to have the same height as the color conversion layer 130. In an embodiment, as Figure 2 and Figure 3 As shown in FIG. 1 , the transmissive member 136 may exist as an empty space without any filling. Figure 2 and Figure 3 As can be seen in FIG. 1 , the transmissive member 136 may not include any additional components, such as quantum dots. In an embodiment, the transmissive member 136 may include quantum dots to emit light converted into a specific wavelength like the first color conversion layer 132 and the second color conversion layer 134, and may also include the above-mentioned light scatterer.

[0107] Figure 4 is based on Figure 2 and Figure 3 A cross-sectional view of a modified embodiment of FIG. Figure 41 is a cross-sectional view showing an example in which the low refractive index layer 120 can be formed on both the upper surface and the lower surface of the color conversion layer 130. Except that the low refractive index layer 120 is formed on both the upper surface and the lower surface of the color conversion layer 130, the remaining components are the same as Figure 2 and Figure 3 The components described in , and therefore, their detailed description will not be repeated. Figure 4 The inclusion of low refractive index layer 120 on both the upper and lower surfaces of color conversion layer 130 as shown in FIG. 1 may help ensure that the luminous efficiency of color conversion panel 100 may be further improved.

[0108] Figure 5 is based on Figure 2 A cross-sectional view of a modified embodiment of FIG. Figure 5 The color conversion panel 100 according to a modified embodiment may further include a first top cover layer 150 and a second top cover layer 160 . Figure 5 A modified embodiment including both the first capping layer 150 and the second capping layer 160 is shown, but either one of the first capping layer 150 and the second capping layer 160 may also be omitted.

[0109] The first capping layer 150 may be formed on the planarization layer 140 and may cover the planarization layer 140. In an embodiment, the first capping layer may be formed after forming the planarization layer 140. The first capping layer 150 may be formed over the entire surface of the substrate 110.

[0110] The second capping layer 160 may be formed between the low refractive index layer 120 and the color conversion layer 130, and may be formed on the entire surface of the substrate 110 like the first capping layer 150. In an embodiment, the second capping layer 160 may be formed between the formation process of the low refractive index layer 120 and the formation process of the color conversion layer 130.

[0111] The first cap layer 150 and the second cap layer 160 may also be made of a material with a low refractive index (eg, SiN x ). The first cap layer 150 that may form an interface with the planarization layer 140, and the second cap layer 160 that may be located between the low refractive index layer 120 and the planarization layer 140 or between the low refractive index layer 120 and the color conversion layer 130 and may form an interface with the low refractive index layer 120, the planarization layer 140, and the color conversion layer 130 may also be made of a material with a low refractive index, and thus may minimize light that may be reflected or scattered incident on the first cap layer 150 and the second cap layer 160. In an embodiment, a color conversion panel 100 with improved light efficiency may be provided by minimizing optical loss at the interface.

[0112] In the case where the color conversion panel 100 includes the first and second capping layers 150 and 160 , the luminous efficiency may be increased by more than 150% compared to the color conversion panel 100 not including the low refractive index layer 120 , the first and second capping layers 150 and 160 at all.

[0113] The color conversion panel 100 and the manufacturing method thereof according to some embodiments have been described above, and thus, a color conversion panel 100 including quantum dots and the like can be provided, in which the light emission efficiency of the quantum dots can be improved.

[0114] Some embodiments provide a display device including the color conversion panel according to the aforementioned embodiments.

[0115] The display device may be a display device using quantum dots, OLED, mini light emitting diode (LED), micro LED, nanorod LED, etc., or a flexible display device.

[0116] The following examples and comparative examples are provided to highlight the characteristics of one or more embodiments, but it should be understood that the examples and comparative examples should not be interpreted as limiting the scope of the embodiments, and the comparative examples should not be interpreted as exceeding the scope of the embodiments. In addition, it should be understood that the embodiments are not limited to the specific details set forth in the examples and comparative examples.

[0117] Examples

[0118] Synthesis Example 1: Preparation of Siloxane Copolymer (A)

[0119] 99.34 g (0.4 mol) of methacryloyloxypropyltrimethoxysilane (MPTMS), 104.16 g (0.5 mol) of tetraethylorthosilicate (TEOS), 12.0 g (0.1 mol) of dimethyldimethoxysilane (DMDMS) and 192.40 g of propylene glycol methylether acetate (PGMEA) were added to a flask, and an aqueous hydrochloric acid solution prepared by dissolving 0.093 g (286 ppm) of hydrochloric acid in 33.10 g of water was added thereto over a period of 10 minutes while stirring at room temperature. Subsequently, after the flask was placed in an oil bath at 60° C. and stirred for 180 minutes, 67.3 g of reaction byproducts (e.g., methanol, ethanol, aqueous hydrochloric acid solution, and water) were discharged from the flask by using a vacuum pump and a Dean-Stark apparatus for 180 minutes, thereby obtaining a siloxane copolymer (A) solution as a product. In the solution, the solid concentration of the siloxane copolymer (A) was 22% by weight. The polystyrene-equivalent weight average molecular weight of the obtained siloxane copolymer (A) was 4,000 g / mol. The weight average molecular weight was measured using gel permeation chromatography (GPC (gel permeation chromatography): HLC-8220GPC, Tosoh Corp.).

[0120] Synthesis Example 2: Preparation of Siloxane Copolymer (B)

[0121] Except for using 99.34g (0.4mol) of MPTMS, 114.576g (0.55mol) of TEOS and 6.0g (0.05mol) of DMDMS, a siloxane copolymer (B) solution was obtained in the same manner as in Synthesis Example 1. In the solution, the solid concentration of the siloxane copolymer (B) was 20 wt%. The polystyrene-converted weight average molecular weight of the obtained siloxane copolymer (B) was 4,000g / mol. The weight average molecular weight was measured using gel permeation chromatography (GPC: HLC-8220GPC, Tosoh Corporation).

[0122] Synthesis Example 3: Preparation of Siloxane Copolymer (C)

[0123] Except for using 99.34g (0.4mol) of MPTMS, 122.9g (0.59mol) of TEOS and 1.2g (0.01mol) of DMDMS, a siloxane copolymer (C) solution was obtained in the same manner as in Synthesis Example 1. In the solution, the solid concentration of the siloxane copolymer (C) was 20 wt%. The polystyrene-converted weight average molecular weight of the obtained siloxane copolymer (C) was 4,000g / mol. The weight average molecular weight was measured using gel permeation chromatography (GPC: HLC-8220GPC, Tosoh Corporation).

[0124] Comparative Synthesis Example 1: Preparation of Siloxane Copolymer (D)

[0125] Except using 99.34g (0.4mol) of MPTMS, 83.328g of TEOS and 24.0g (0.2mol) of DMDMS, a siloxane copolymer (D) solution was obtained in the same manner as in Synthesis Example 1. In the solution, the solid concentration of the siloxane copolymer (D) was 20 wt%. The polystyrene-converted weight average molecular weight of the obtained siloxane copolymer (D) was 4,000 g / mol. The weight average molecular weight was measured using gel permeation chromatography (GPC: HLC-8220GPC, Tosoh Corporation).

[0126] Comparative Synthesis Example 2: Preparation of Siloxane Copolymer (E)

[0127] A siloxane copolymer (E) was prepared in the same manner as in Comparative Synthesis Example 1, except that a 100 ppm tetramethylammonium hydroxide (TMAH) aqueous solution was added to the solution containing the silane monomer mixture instead of the hydrochloric acid aqueous solution to carry out polymerization.

[0128] The polystyrene-equivalent weight average molecular weight of the siloxane copolymer (E) obtained by the reaction was 4,000 g / mol. The weight average molecular weight was measured using gel permeation chromatography (GPC: HLC-8220GPC, Tosoh Corporation).

[0129] Synthesis Example 4: Preparation of Surface-treated Hollow Silica Particles

[0130] The average particle size (D 50 ) is 100 nm and surface-treated with methacryloxypropyltrimethoxysilane (silica solid content 20%, L0516, Nano Advanced Materials Co., Ltd.).

[0131] Examples 1 to 3 and Comparative Examples 1 and 2: Preparation of Curable Resin Compositions

[0132] Each of the siloxane copolymer solutions according to Synthesis Examples 1 to 3, the hollow silica particle dispersion according to Synthesis Example 4 (silica solid content: 20%, L0516, Nano Advanced Materials Co., Ltd.), PGMEA as a solvent, and F-563 (DIC Co., Ltd.) as a fluorine-containing surfactant were mixed in the ratios shown in Table 1, based on the total weight of each composition, to prepare curable resin compositions according to Examples 1 to 3.

[0133] In addition, in the same manner as the method of preparing the curable resin compositions according to Examples 1 to 3, each curable resin composition according to Comparative Examples 1 and 2 was prepared using the solutions according to Comparative Synthesis Examples 1 and 2 as the siloxane copolymer solution, respectively.

[0134] Preparation and evaluation of cured layer

[0135] Each of the compositions according to Examples 1 to 3 and Comparative Examples 1 and 2 was formed into a cured layer, and the refractive index, haze, crack margin, and indentation hardness of each of the cured layers were measured, and the results are shown in Table 1. In addition, whether the panel including each of the cured layers was cracked was inspected, and the results are shown in Table 1. The thickness of each of the cured layers was measured by using an Alpha-step (surface profiler, KLA-Tencor Corp.), and each evaluation was performed according to the following method.

[0136] (1) Refractive index

[0137] Each of the compositions according to the examples and comparative examples was applied to a silicon wafer having a diameter of 4 inches by using a spin coater (Opticoat MS-A100, Mikasa Co., Ltd.), and then pre-baked on a hot plate at 100° C. for 2 minutes to form a film. Subsequently, the film was cured at 230° C. for 20 minutes and dried to obtain each 2.0 μm thick cured layer. The refractive index of each obtained cured layer was measured at 550 nm by using an ellipsometer (Base-160, JA Woollam), and the results are shown in Table 1.

[0138] (2) Haze

[0139] Except that each of the compositions according to the examples and comparative examples was spin-coated on a glass substrate instead of a silicon wafer, each cured layer having a thickness of 2.0 μm was obtained in the same manner as the method for producing a cured layer for measuring a refractive index. The haze of each obtained cured layer was measured using a haze meter at a wavelength of 650 nm, and the results are shown in Table 1.

[0140] (3) Crack allowance

[0141] The crack margin refers to the crack initiation thickness of each solidified layer. If the solidified layer formed of the curable resin composition including the siloxane copolymer becomes thicker than a predetermined thickness, the solidified layer may be broken. Therefore, when the crack initiation thickness of the solidified layer is thicker, the crack margin may be larger, which means that fewer cracks may appear on the corresponding solidified layer.

[0142] Like the method for measuring haze, the method for measuring crack margin is implemented by spin coating each of the curable resin compositions according to the examples and comparative examples on a glass substrate and curing it to obtain a cured layer. In this article, if the cured layer is not broken, a part of the cured layer is cut off using a blade, and then the thickness is measured using a KLA P-6 manufactured by Tencor Corp. Subsequently, in order to make the cured layer thicker, each of the resin compositions is more thickly coated and then cured to check whether the corresponding cured layer is broken. In this way, the maximum thickness of the cured layer before cracks occur is measured as a crack margin, and the results are shown in Table 1.

[0143] (4) Indentation hardness

[0144] In the same manner as the method for producing a cured layer for measuring the refractive index, each of the curable resin compositions according to the examples and comparative examples was coated on a silicon wafer and cured to obtain each cured layer having a thickness of about 2.0 μm. The indentation hardness was measured by pressing the cured layer at 100 μN using a nanoindenter, and the results are shown in Table 1.

[0145] Table 1

[0146]

[0147] *Based on the total weight of the curable resin composition.

[0148] As shown in Table 1, the cured layer formed by the curable resin composition according to Examples 1 to 3 including the curable resin composition according to some embodiments exhibits a low refractive index of 1.229 or less and thus has low refractive index characteristics, and also exhibits a sufficiently low haze of 1.2 and thus exhibits transparent film characteristics. In addition, the cured layer according to Examples 1 to 3 exhibits a sufficient crack margin of at least 5.8 μm or more and a high pressure scratch hardness of 0.125 GPa or more and thus has sufficient mechanical properties. When such a cured layer is applied as a low refractive index layer of a color conversion panel including a quantum dot (QD) color filter, the panel will not crack even in a high temperature process. Figure 6 is a transmission electron microscope (TEM) image showing a cross section of a cured layer according to Example 3, in which the cured layer is not broken even at a thickness of about 4 μm or more.

[0149] On the other hand, the cured layer formed by the curable resin composition of Comparative Example 1 exhibits a refractive index of 1.231 or less and thus exhibits low refractive index characteristics, and also exhibits a low haze of 0.8 and thus exhibits excellent optical properties. In addition, the cured layer exhibits a very high crack margin of 7.0 μm, but exhibits a relatively low indentation hardness of 0.115 GPa (which is less than 0.12 GPa). Therefore, when the cured layer of Comparative Example 1 is applied as a low refractive index layer of a color conversion panel including a QD color filter, the panel breaks in a high temperature process. In other words, the margin of the cured layer according to Comparative Example 1 itself is high, but when it is processed under a high temperature process to be applied to a panel, the panel breaks. Figure 7 is a scanning electron microscope image showing cracking of a panel to which the cured layer of Comparative Example 1 was applied.

[0150] On the other hand, the curable resin composition according to Comparative Examples 1 and 2 includes a siloxane copolymer having the same components, but since the copolymer of Comparative Example 2 is prepared by adding an alkaline catalyst (TMAH) instead of an acid, unlike Comparative Example 1, the cured layer formed by the copolymer of Comparative Example 2 exhibits different properties from the cured layer of Comparative Example 1. The cured layer of Comparative Example 2 exhibits a low refractive index of 1.22 and thus satisfies the low refractive index characteristics, and additionally exhibits a very low haze of 0.6 and thus exhibits excellent optical properties. In addition, the cured layer itself exhibits a sufficient crack margin of 5.8 μm and a sufficiently high indentation hardness of 0.130 GPa. However, when the cured layer of Comparative Example 2 is processed by a high temperature process to be applied to a color conversion panel including a QD color filter as a low refractive index layer, the panel breaks, similar to the cured layer of Comparative Example 1. Figure 8 is a scanning electron microscope (SEM) image showing cracking of the panel to which the cured layer of Comparative Example 2 was applied.

[0151] Therefore, the cured layer according to Example 1 to Example 3 including the curable resin composition according to some embodiments realizes low refractive index and low haze and therefore satisfies excellent optical properties, provides sufficient crack margin and exhibits high pressure mark hardness, and therefore exhibits excellent mechanical properties. In addition, even if these cured layers are applied to the substrate including the pattern (e.g., QD color filter) at the bottom and therefore have a step and subject these cured layers to a high temperature process, cracks will not occur during the manufacture of the panel. Therefore, the curable resin composition according to some embodiments has excellent optical properties and mechanical properties, but cracks do not occur even in a high temperature process, and therefore the results prove that the curable resin composition is advantageously used as a low refractive index layer material for various display devices.

[0152] One or more embodiments may provide a curable resin composition that may be excellent in both optical characteristics (eg, low refractive index and high transparency) and mechanical properties (eg, high pressure scratch hardness and crack resistance).

[0153] Some embodiments may provide a thin layer produced by curing the composition.

[0154] Some embodiments may provide a color conversion panel including the thin layer.

[0155] Some embodiments may provide a display device including the color conversion panel.

[0156] The curable resin composition according to some embodiments can be cured at low temperatures, and a thin layer made from the curable resin composition can have excellent optical properties (e.g., low refractive index and low haze) and excellent mechanical properties (e.g., high pressure scratch hardness and crack resistance). Therefore, a thin layer made from the composition according to some embodiments can be advantageously used in various display devices.

[0157] Exemplary embodiments have been disclosed herein, and although specific terms are employed, they are used and interpreted in a general and descriptive sense only and not for purposes of limitation. In some cases, it will be apparent to one of ordinary skill in the art at the time this application is filed that, unless otherwise specifically stated, features, characteristics, and / or elements described in connection with a particular embodiment may be used alone or in combination with features, characteristics, and / or elements described in connection with other embodiments. Therefore, those skilled in the art will understand that various changes in form and detail may be made without departing from the spirit and scope of the invention as set forth in the claims above.

Claims

1. A curable resin composition comprising: a silicon-containing polymer represented by Chemical Formula 1; hollow particles; and a solvent, [Chemical Formula 1] (R 4 R 5 R 6 SiO 1 / 2 ) M (R 7 R 8 SiO 2 / 2 ) D (R 9 SiO 3 / 2 ) T1 (SiO 3 / 2 -Y-SiO 3 / 2 ) T2 (SiO 4 / 2 ) Q wherein, in Chemical Formula 1, R 4 To R 9 each independently represents hydrogen, or a substituted or unsubstituted C1-C30 alkyl group, a substituted or unsubstituted C2-C30 alkenyl group, a substituted or unsubstituted C2-C30 alkynyl group, a substituted or unsubstituted C1-C30 heteroalkyl group, a substituted or unsubstituted C6-C30 aryl group, a substituted or unsubstituted C3-C30 cycloalkyl group, a substituted or unsubstituted C2-C30 heterocycloalkyl group, a substituted or unsubstituted C1-C30 alkoxy group, a carboxyl group, R(C═O)—, R(C═O)O—, wherein R is hydrogen, a C1-C30 alkyl group, a C3-C30 cycloalkyl group, a C6-C30 aryl group, or a combination thereof, an epoxy-containing monovalent organic group, a (meth)acryloyloxy group, a (meth)acrylate group, an aminoalkyl group, or a combination thereof, Y is a substituted or unsubstituted C1 to C30 alkylene group, a substituted or unsubstituted C2 to C30 alkenylene group, a substituted or unsubstituted C3 to C30 cycloalkylene group, a substituted or unsubstituted C6 to C30 arylene group, or a combination thereof, 0 ≤ M ≤ 0.2, 0 < D < 0.2, 0.1 < T1 ≤ 0.5, 0 ≤ T2 ≤ 0.2, 0 ≤ Q ≤ 0.65, and M + D + T1 + T2 + Q = 1.

2. The curable resin composition according to claim 1, wherein in Chemical Formula 1, 0 ≤ M ≤ 0.1, 0 < D ≤ 0.15, 0.2 ≤ T1 ≤ 0.5, and 0.3 ≤ Q ≤ 0.

65.

3. The curable resin composition according to claim 1, wherein in Chemical Formula 1, 0 ≤ M ≤ 0.1, 0.01 ≤ D ≤ 0.1, 0.3 ≤ T1 ≤ 0.45, and 0.5 ≤ Q ≤ 0.

6.

4. The curable resin composition according to claim 1, wherein the silicon-containing polymer has a polystyrene-equivalent weight average molecular weight of 1,000 g / mol to 100,000 g / mol.

5. The curable resin composition according to claim 1, wherein the silicon-containing polymer is included in an amount of 1 wt% to 50 wt% based on the total weight of the curable resin composition.

6. The curable resin composition according to claim 1, wherein the curable resin composition has a pH of 4 to 10.

7. The curable resin composition according to claim 1, wherein the hollow particles have an average diameter D of 10 nm to 300 nm. 50 .

8. The curable resin composition according to claim 1, wherein the hollow particles have an average porosity of 40% to 90%.

9. The curable resin composition according to claim 1, wherein: the hollow particles are hollow silica, and a silane compound is included on the surface of the hollow silica.

10. The curable resin composition according to claim 1, wherein the hollow particles are included in an amount of 1 wt% to 35 wt% based on the total weight of the curable resin composition.

11. The curable resin composition according to claim 1, further comprising a fluorosurfactant or a silicone surfactant.

12. A thin layer made from the curable resin composition according to claim 1.

13. A color conversion panel including the thin layer according to claim 12.

14. A display device including the color conversion panel according to claim 13.

Citation Information

Patent Citations

  • Organic Light Emitting Diode Display Device And Method Of Driving The Same

    KR1020230096301A